Harnessing mHealth to improve the diabetes screening and diagnosis rate in rural Indian settings: a learning from health systems initiative - Prabhune, Akash Gajanan; Manoharan, Aparna; Arul, Murugan (International Journal Of Community Medicine And Public Health, 2019)
Background: Diabetes forms huge burden of non-communicable diseases that is affecting health care systems in India. India has large number undiagnosed and undetected cases. mHealth initiatives are cost effective, quick and less resource intensive technology assisted initiatives which help to strengthen the health system. High mobile penetration and availability of cheap and high-speed data network across India has been conducive to implement mHealth initiatives in Indian health system. We present our experience in using mHealth initiative to improve the diabetes screening and diagnosis in rural Indian settings. Methods: The study is a descriptive analysis of all the tasks undertaken as part of “Disease free Village” Initiative of our organization. The study data is operational data from our organizational health information management systems. The study is divided into three phase. Phase 1, was dedicated to enrolling entire village population using android smartphone and ODK collect application; phase 2 used clinical decision support system for screening of high risk individuals and phase 3 used traditional door to door campaign to motivating the high risk individuals to get their fast and post prandial blood glucose levels checked at health care facility. Results: Phase 1 was to set a baseline, with 3624 base population, 2651 was target adult population. Rapid screening in phase 2, screened 2204 (83.14%). Out of 2204 screened cases 1307 were high risk cases. 1307 high risk cases were followed in Phase 3, and blood glucose screening was carried out 1156 (88.44%) high and moderate risk individuals out of 1307 (100%). Conclusions: We concluded that the mHealth initiatives for screening and diagnosis of diabetes in rural India, combined with traditional techniques could help to improve screening and diagnosis rate and help to reduce the hidden burden of disease.